A Escola Maternal e Creche Votorantim: concepções e práticas pedagógicas - de 1925 a 1935. - Garcia, Maria Clara Coimbra (Universidade Federal de São Carlos, 2025)
This research proposes a study on the historical constitution of the Votorantim Nursery School, considering its historical uniqueness, marked by the fact that it was the birthplace of one of the first nursery schools in the state of São Paulo. The focus is on the mapping, investigation and analysis of the conceptions and pedagogical practices pointed out in the written records of the school inspectors who left their notes in the terms of visit between the years 1925 and 1935, especially the observations of the Special Inspector of Nursery Schools Joana Grassi Fagundes. To this end, records and official documents, news published in local newspapers and images that may report to the time studied will be used as documentary sources. The dialogue between the sources will contribute to the composition of the scenario of the Votorantim Nursery School and Nursery. This research is also committed to contributing to the reflective process in the training of teachers, who will be able to establish a relationship between the educational methodologies of the past and current practices.
Votorantim Nursery School and Daycare Center: pedagogical concepts and practices - from 1925 to 1935.
Keywords: educação operária; história da educação infantil; Escola Maternal e Creche Votorantim; Joana Grassi Fagundes; práticas pedagógicas; working class education; history of early childhood education; Votorantim Nursery School and Daycare Center; pedagogical practices.; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS HUMANAS::HISTORIA